The Proposed Quality Improvement of Incense Products Using the Six Sigma Method at UD. Dupa Karya Mandiri - Fearnanda, Yuanita Lucky; Zunaidi, Rizqa Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
In 2023, Indonesia's Hindu population accounted for approximately 1.7% of the total population, equating to roughly four million individuals within a populace of 250 million. UD. Dupa Karya Mandiri being a prominent producer of incense products in high demand. However, during the 2023 Chinese New Year (Imlek) and Nyepi celebrations, expected to spur increased demand, the market witnessed a downturn due to a surge in defective product rejection. This study aims to describe the factors that cause product defects, measure the level of sigma level in incense production, then proceed with efforts to improve product quality. Six Sigma methodology is used to handle this problem, this study employs the Six Sigma methodology. The analysis yielded a sigma value of 2.1 and a DPMO (Defects Per Million Opportunities) value of 289,228.10, signifying the necessity of further enhancement in quality to reduce the number of defective products and elevate the sigma value. Therefore, this research gives recommendations for improvement to UD. Dupa Karya Mandiri includes SOPs for Drying, Understanding the Production Process, Machine Maintenance, Bamboo Encek Replacement and Monthly Production Reports.